A Modeling Framework for Coordinating Promotion and Production Decisions within a Firm - Sogomonian, Aram G.; Tang, Christopher S. (Management Science, 1993)
This paper presents a modeling framework for evaluating the benefits of coordinating promotion and production decisions over a finite planning horizon within a firm. These decisions include the timing and level of promotion, and the level of production. The modeling framework consists of the development of a baseline model and an integrated model. In the baseline (integrated) model, the firm would consider those promotion and production decisions separately (jointly). For each of the models, we formulate the problem that determines the optimal promotion and production decisions so that the total net profit is maximized as a mixed integer program. By exploiting the structure of the problem, we show that each problem can be reformulated as a “longest path” problem over a network. Hence, each problem can be solved efficiently. This solution approach enables us to evaluate the benefits of coordinating promotion and production decisions by comparing the total net profit generated by the baseline model to that of the integrated model.